MANAJEMEN TALENTA APARATUR SIPIL NEGARA: PRAKTIK DAN PELUANG INOVASI - Bhakti Gusti Walinegoro; Junaidul Fitriyono (Jurnal Manajemen Kepegawaian, 2023)
The talent management of the state civil apparatus is the main effort to realize a world-class state civil apparatus. In Indonesia, the practice has been carried out through various programs and stages. However, there are still obstacles that become challenges, which can actually be opportunities for innovation. This study aims to analyze the practices and opportunities for innovation of state civil apparatus talent management in Indonesia. The discussion focuses on three main scopes in talent management, namely recruitment and selection, training and development, and talent retention. The method used is descriptive qualitative. The research data comes from documents in the form of journal articles related to the research topic, such as report about state civil apparatus and trusted mass media news. The results of the analysis show that state civil apparatus talent management carried out in Indonesia is still not optimal. Therefore, it is necessary to make improvements through innovation strategies by utilizing existing potentials or opportunities. In recruitment and selection, improvements can be made by improving branding to attract potential applicants and recruiting professionals for certain positions. In training and development, improvement can be done by planning and implementing competency-based training and digitizing career development. In talent retention, improvements can be made from the aspects of leadership commitment, awarding, and career certainty.